2003
DOI: 10.1046/j.1472-8206.2003.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal amphotericin B in the treatment of visceral leishmaniasis in immunocompetent patients

Abstract: The leishmaniases are protozoan diseases caused by Leishmania parasites. The first-line treatment of its visceral forms is pentavalent antimony (meglumine antimoniate or sodium stibogluconate), but toxicity is frequent with this drug. Moreover antimony unresponsiveness is increasing in Leishmania infantum and L. donovani foci, both in immunocompetent and in immunosuppressed patients. Amphotericin B is a polyene macrolide antibiotic that binds to sterols in cell membranes. It is the most active antileishmanial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…12 Amphotericin B deoxycholate and lipid-based amphotericin B products are well-established treatments for visceral leishmaniasis. 13 The latter formula is considered less nephrotoxic than nonliposomal amphotericin B because it specifically targets the macrophages in which the Leishmania parasites develop. 14 In our study, a dose of 3 mg/kg of the liposomal amphotericin (AmBisome) was given for 5 consecutive days, with a sixth dose on day 10.…”
Section: Discussionmentioning
confidence: 99%
“…12 Amphotericin B deoxycholate and lipid-based amphotericin B products are well-established treatments for visceral leishmaniasis. 13 The latter formula is considered less nephrotoxic than nonliposomal amphotericin B because it specifically targets the macrophages in which the Leishmania parasites develop. 14 In our study, a dose of 3 mg/kg of the liposomal amphotericin (AmBisome) was given for 5 consecutive days, with a sixth dose on day 10.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 95% efficacy was achieved with higher single doses (10 mg/kg) or when used in combination with miltefosine or paromomycin [10]. Although licensed and recommended for first-line treatment of VL in immunocompetent patients [11], Ambisome® use in eastern Africa has been mostly limited to second line treatment in a few centres mainly due to its high cost and cold storage requirements [12]. A small study with AmBisome® conducted in Kenya indicated higher doses were required than had been used in studies in India.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has recently been suggested that AMB should replace antimonials as the drug of choice in Bihar (37). In addition, patients coinfected with Leishmania infantum visceral leishmaniasis and human immunodeficiency virus in resource-rich countries are usually treated with liposome-entrapped AMB (8,27). Guidelines for treatment with AMB and other antileishmanial drugs have been improved, which, in addition to better treatment of individual patients, should lead to fewer relapses and therefore a decreased risk of secondary resistance.…”
mentioning
confidence: 99%